2021
DOI: 10.1177/00938548211028895
|View full text |Cite
|
Sign up to set email alerts
|

The Keepers: Returning Citizens’ Experiences With Prison Staff Misconduct

Abstract: Correctional staff play a major role in the incarceration experience for millions of U.S. adults each year. While much research has addressed misconduct perpetrated by incarcerated persons, less has systematically addressed rule-violating behavior by correctional staff and how such conduct is perceived by formerly incarcerated individuals. Using qualitative data gathered from 38 interviews with men and women recently released from prison, we examine their experiences with prison staff misconduct. Respondents s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Correctional staff is entrusted to maintain order and safety within correctional facilities, which includes the important step of modeling prosocial behaviors (Dowden & Andrews, 2004). Assaultive behavior by staff threatens the legitimacy of correctional facilities and contributes to institutional violence (Novisky et al, 2022). Training protocols should ensure staff is trained not only during onboarding but also over time on (a) recognizing and responding to the signs and symptoms of mental illness; and (b) recognizing and addressing racial biases among staff, including implicit biases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Correctional staff is entrusted to maintain order and safety within correctional facilities, which includes the important step of modeling prosocial behaviors (Dowden & Andrews, 2004). Assaultive behavior by staff threatens the legitimacy of correctional facilities and contributes to institutional violence (Novisky et al, 2022). Training protocols should ensure staff is trained not only during onboarding but also over time on (a) recognizing and responding to the signs and symptoms of mental illness; and (b) recognizing and addressing racial biases among staff, including implicit biases.…”
Section: Discussionmentioning
confidence: 99%
“…When one appears weak, potential offenders—either other incarcerated individuals or correctional staff—may view the risk of retaliation to be low. Novisky et al (2022), for example, found that formerly incarcerated women identified mental illness as a risk factor for staff-perpetrated sexual violence. Similarly, McNeeley (2021) found that individuals displaying symptoms of mental illness were more likely to be involved in a use of force incident including the use of pinion restraints, cell extraction, and physical force.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially important given the small number of datasets inclusive of individual-level data of older adults who are incarcerated (Ahalt et al , 2013). Further, available data from persons who are incarcerated may be less reliable or valid due to low trust in staff (Novisky et al , 2021), limited understanding of one’s experience or internalized oppression (Porter, 2019). Stigma on behalf of the provider may also shape perceived or actual dual loyalty to patients and prison authorities (Glowa-Kollisch et al , 2015), which can also influence validity.…”
Section: Standardized Outcome Measuresmentioning
confidence: 99%